Asiatic acid induces endoplasmic reticulum stress and apoptotic death in glioblastoma multiforme cells both in vitro and in vivo. Issue 11 (22nd September 2014) - Kavitha, Chandagirikoppal V.; Jain, Anil K.; Agarwal, Chapla; Pierce, Angela; Keating, Amy; Huber, Kendra M.; Serkova, Natalie J.; Wempe, Michael F.; Agarwal, Rajesh; Deep, Gagan
<x xml:space="preserve">Abstract</x> Glioblastoma multiforme (GBM) is an untreatable malignancy. Existing therapeutic options are insufficient, and adversely affect functional and non‐cancerous cells in the brain impairing different functions of the body. Therefore, there is an urgent need for additional preventive and therapeutic non‐toxic drugs against GBM. Asiatic acid (AsA; 2, 3, 23‐trihydroxy‐12‐ursen‐28‐oic acid, C30H48O5) is a natural small molecule widely used to treat various neurological disorders, and the present research investigates AsA's efficacy against GBM both in vitro and in vivo. Results showed that AsA treatment (10–100 µM) decreased the human GBM cell (LN18, U87MG, and U118MG) viability, with better efficacy than temozolomide at equimolar doses. Orally administered AsA (30 mg/kg/d) strongly decreased tumor volume in mice when administered immediately after ectopic U87MG xenograft implantation (54% decrease, P ≤ 0.05) or in mice with established xenografts (48% decrease, P ≤ 0.05) without any apparent toxicity. Importantly, AsA feeding (30 mg/kg/twice a day) also decreased the orthotopic U87MG xenografts growth in nude mice as measured by magnetic resonance imaging. Using LC/MS‐MS methods, AsA was detected in mice plasma and brain tissue, confirming that AsA crosses blood‐brain barrier. Mechanistic studies showed that AsA induces apoptotic death by modulating the protein expression of several apoptosis regulators (caspases, Bcl2 family members, and survivin) in GBM cells. Furthermore, AsA induced ER stress (increased GRP78 and Calpain, and decreased Calnexin and IRE1α expression), enhanced free intra‐cellular calcium, and damaged cellular organization in GBM cells. These experimental results demonstrate that AsA is effective against GBM, and advocate further pre‐clinical and clinical evaluations of AsA against GBM. © 2014 Wiley Periodicals, Inc.